Small Bowel Volvulus: A Case Report - Patial, Tushar (Cureus, 2017)
Small bowel volvulus is a rare clinical entity which presents as recurrent intermittent abdominal pain after consumption of food. Although the entity is well described in the literature, diagnosis is often difficult due to its clinical presentation being similar to mesenteric ischemia. Herein we present the case of a 44-year-old male who presented to us with this condition.